Socrealizm od środka. Design, sztuka wnętrza i modernizacja - Sumorok, Aleksandra (Artium Quaestiones, 2021)
The article focuses on interior design from the first half of the 1950s. The interior spaces realized at that time in Poland elude unambiguous classifications, both in terms of formal and ideological aspects. I propose to look at the interiors from this time not in terms of style (difficult, complex, hybrid), but in a broader sense, as a political, socio-cultural phenomenon. The interiors were supposed to favor social modernization (assumed in the communist project), especially the idea of promotion and changing class habitus. They precisely modeled new forms of social life (cultural spaces), as well as family life, as they defined the way of eating, “being” (gastronomic interiors), spending free time and holidays. The leap into modernity was particularly noticeable in the architecture and interiors with which everyone interacted on a daily basis. Indicating the participation of interiors in the multifaceted modernization process can make us realize the complexity of the post-war reality, including the interior design from the first half of the 1950s, which was related to many spheres of social and cultural life.